Conceptual, Linguistic and Pedagogical Aspects of Humanitarian World Picture - Galiakberova, Alfinur A.; Asratyan, Norair M.; Asratyan, Zoya D.; Mukhametshin, Azat G. (Journal of History Culture and Art Research, 2018)
The modern world faces numerous challenges that ultimately have a worldview nature. Every person included in the global processes meets with many contradictions, the settlement of which determines the direction of different communities and the whole of mankind movement. Globalization which began and was initially conceived as a process of world economic, political, cultural integration, rapprochement of peoples, over time began to demonstrate its negative aspects: socio-cultural unification, standardization of human tastes and preferences, stereotyping of people’s habits and behavior, weakening of traditional values and ties. At present globalization is opposed to a relatively new process of extending glocalization as the desire to avoid the extremes of globalization, to prevent the disappearance of regional differences, to preserve and strengthen economic independence and cultural identity. This inevitably puts a human being and the whole mankind not only in front of the need of extensive scientific, technical and technological, social and humanitarian knowledge, but also requires the development of the ability to comprehend the whole array of diverse knowledge obtained in order to efficiently, in activity-based way use them. Therefore, alongside with general ideas about the world, the important task is integration of diverse modern humanitarian knowledge into the overall humanitarian picture of the world. The article examines some key methodological issues of the formation of the humanitarian world picture, including the problems of the language worldview, and focuses on the teaching of the experimental course "Humanitarian picture of the world" in the framework of the model of practice-oriented training of Russian pedagogical staff.